Facial Emotion Recognition: Virtual Reality Program for Facial Emotion Recognition—A Trial Program Targeted at Individuals With Schizophrenia. (January 2020) - Souto, Teresa; Silva, Hugo; Leite, Angela; Baptista, Alexandre; Queirós, Cristina; Marques, António
People with severe mental illness (SMI), schizophrenia in particular, show considerable functional impairment in emotional recognition and social perception, which negatively affects interpersonal relationships and social functioning. Owing to its ecological validity, virtual reality (VR) has been observed to improve both assessment and training of emotional recognition skills of people with SMI. This article includes two studies: (a) a descriptive study on the Virtual Reality program for Facial Emotion Recognition (VR-FER) and (b) an empirical study that presents the results of the application of the VR-FER's first module. For the second study, data were collected using two samples: a group of 12 people with schizophrenia and a reference group of 12 people who were mentally healthy. Data analysis comprised descriptive (mean, standard deviation) and inferential statistics (Mann–Whitney U test). Results showed that the first group presented a lower number of correct answers and a higher number of incorrect answers compared with the second group regarding facial emotion recognition (FER), thereby confirming the need to develop strategies to improve emotional recognition and social perception in people with schizophrenia. VR-FER is regarded a strategic training program for FER, using latest technology and following rehabilitation guidelines for SMI.